Environmental education from an intercultural approach: A glimpse into Latin America - Helio Manuel García-Campos (Environmental Association of Southern Africa, 2019)
Latin America has established a new model of higher education termed intercultural, or indigenous, education. This essay analyses the potential that the integration of educational approaches focused on environmental sustainability and linked to intercultural education approaches could represent to Latin American institutions. The trend has set a new direction and opened up perspectives on integrating other fields, such as ethnoscience, agroecology, education and applied anthropology. Different aspects of the relationship between culture and nature are analysed, bearing in mind that biocultural diversity and its territorial expressions are part of a heritage that rural and indigenous societies present as a contribution to the current definition of civilizatory trends. Based on this review, the paper presents a comparative and integrative conceptual framework that can be used as a reference for practical applications of experience or as a search tool for educational alternatives that can bridge the gap between environmental and interculturalÂ education.